Analysis of Peripapillary and Macular Choroidal Thickness in Eyes with Pseudoexfoliative Glaucoma and Fellow Eyes. (8th June 2020) - Li, Fan; Shang, Qingli; Tang, Guangxian; Zhang, Hengli; Yan, Xiaowei; Ma, Lihua; Geng, Yulei; Zhang, Qing
Abstract : Purpose . To compare differences in peripapillary and macular choroidal thickness in pseudoexfoliative glaucoma (PXG) eyes, nonexfoliative fellow eyes, and normal eyes. Methods . This case-control study included 37 PXG patients (group A: 37 PXG eyes; group B: 37 nonexfoliative fellow eyes) and 37 sex-, age-, and axial length-matched healthy volunteer eyes (group C). Peripapillary and macular choroidal thickness and volume were measured in all subjects via enhanced-depth imaging-optical coherence tomography. Results . The average peripapillary (AP) choroidal thickness was (130.10 ± 46.14) μ m, (131.43 ± 46.00) μ m, and (147.89 ± 53.32) μ m; average macular (AM) choroidal thickness was (191.72 ± 68.07) μ m, (204.62 ± 69.54) μ m, and (215.10 ± 45.40) μ m; and average volume was (0.59 ± 0.21) μ m 3, (0.63 ± 0.21) μ m 3, and (0.65 ± 0.14) μ m 3 in groups A, B, and C, respectively. NIP choroidal thickness was significantly lower in groups A and B than in group C (P < 0.05 ). TIM and TOM choroidal thickness and volume were significantly lower in group A than in group C (P < 0.05 ). NIM, SIM, NOM, IOM, AM choroidal thickness and volume, and CSM choroidal thickness were significantly lower in group A than in group B (P < 0.05 ). CSM, TIM, and TOM in group A and TIM, TOM choroidal thickness, and volume in group B were significantly lower than in group C (P < 0.05 ). Conclusions . NIP choroidal thickness in PXG eyes and nonexfoliative fellow eyes and temporal macular choroidal thickness in PXG eyes were significantly lower than in normal eyes. Macular choroidal thickness (except in temporal regions) was significantly lower in PXG eyes than in nonexfoliative fellow eyes. Changes in peripapillary and macula choroidal thickness further elucidate the choroid's role in PXG development and progression.